THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON EMPLOYEE’S JOB SATISFACTION - Omer, Soran Kakarash (Journal of process management and new technologies, 2018)
Abstract This study purposes at examining the impact of corporate social responsibility (CSR) on employee job satisfaction, it is an exploratory study about employee’s opinion toward CSR activities of Paky hospital. The CSR is the independent variable and employee’s job satisfaction is the dependent variable. This study also aims of check the availability of CSR activities and evaluates its effect in the hospital. A questionnaire involving of eight items and has been set and distributed among the employees of Paky hospital randomly. We have used One-Sample Statistics t-test and ANOVA with the program SPSS.v.20 to test the validity of our hypothesis. The main conclusion of the study is there has the insignificant effect of CSR activities on job satisfaction of employees in Paky hospital; as well some of the elements or activities of CSR and job satisfaction are shared in the hospital.